Exploration of Engineered Diode Current-Voltage Convergence for Maximum Power Point Tracking in Single-Axis Solar Tracker Systems. - Novita Asma Ilahi; Afrizal Abdi Musyafiq; Fadhillah Hazrina (Jurnal E-Komtek, 2025)
Indonesia, situated in the tropics, possesses optimal solar irradiation potential, positioning it as an ideal location for the deployment of photovoltaic (PV) energy systems. Given the escalating electricity demand driven by demographic expansion and technological advancements, harnessing solar panels as a viable alternative energy source is crucial. Nevertheless, static PV installations frequently yield suboptimal power absorption. This research, titled "Exploration of Diodic Current-Voltage Convergence of Maximum Power Point Engineering in a Single-Axial Solar Tracker System," focuses on an advanced approach to power optimization. Specifically, the study designs and evaluates a system capable of optimally capturing solar radiation by integrating a 20 Watt Peak (WP) PV unit with an automatic Solaris Single-Axial Tracker. The system architecture utilizes an Arduino Nano microcontroller as the core control unit, which is equipped with an ACS712 current sensor and a DC voltage sensor. Real-time data communication is accomplished using a Node-MCU ESP8266 module for serial transmission. Comparative analysis reveals a significant performance enhancement in the PV system attributed to the automatic tracking implementation. The average power absorbed by the 20 WP solar panel increased from 89.2 W (without tracking) to 93.70 W when the Single-Axial Tracking system was employed. Correspondingly, the PV panel's efficiency improved from 78.4% (static) to 82% (tracked). Furthermore, the monitoring data (current, power, and voltage) is visualized in real-time on a smartphone via the Blynk application, enabled by an internet-based communication protocol. This investigation successfully demonstrates that a microcontroller-based single-axial tracking system offers an efficient solution for maximizing solar energy absorption in tropical environments.